Differentiating between girls and boys in transition through smoking stages: A sex-specific growth mixture modeling - Nasrin Jafari; Asghar MohammadpourAsl; Mohammad Asghari-Jafarabadi (Tabriz University of Medical Sciences, 2021)
Background: Smoking is a complex process, and adolescents pass through a number of different stages on the way to become smokers and it is sex-dependent. Methods: In this cohort study, the illustrative samples of 10th-grade students (2241 girls and 2956 boys) were assessed using a multistage sampling in Tabriz, Iran. The main variables of the study were smoking status, intention to start smoking, and smoking during the past week/ month, which were collected using a valid and reliable instrument. Sex-specific GMMs were fitted to assess the transition through smoking stages. Results: GMMs lead in a 2-class optimal model: "Occasional/Intending smokers" and "Non-smokers". GMMs indicated that girls had lower levels of smoking status, intention to start smoking, smoking during the past week/month in both classes (significant and negative intercepts: -8.5 to -0.6). In addition, transitions toward higher levels of smoking status, intention to start smoking, smoking during the past week/month were observed in both classes for boys, but in the second class for girls (significant and positive slopes: 0.2 to 2.7). Conclusion: This study highlighted the importance of stopping the initiation and avoiding transition through smoking stages with special sex-specific planning in the future.